The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/healthcare11070972
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Determinants of COVID-19 Vaccine Acceptance, Uptake, and Hesitancy in the Pediatric Population: A Study of Parents and Caregivers in Saudi Arabia during the Initial Vaccination Phase

Abstract: Objectives: This study aims to assess COVID-19 vaccine acceptance, uptake, and hesitancy among parents and caregivers of children in Saudi Arabia during the initial rollout of pediatric COVID-19 vaccination. Methods: An electronic survey was used to collect data from participants who visited a COVID-19 vaccine center. The survey included demographic data, COVID-19 vaccine status among participants and their children, and reasons for vaccine acceptance or rejection. The Vaccine Hesitancy Scale (VHS) tool was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Indeed, attitudes such as perceived benefit and risk have been shown to be related to HPV vaccination acceptance [ 60 , 61 ]. Our findings are consistent with similar patterns observed in COVID-19 vaccination, with hesitancy linked to concerns about effectiveness, safety, and necessity [ 62 ]. Communication programs focusing on individual benefits can increase vaccine intention and uptake.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, attitudes such as perceived benefit and risk have been shown to be related to HPV vaccination acceptance [ 60 , 61 ]. Our findings are consistent with similar patterns observed in COVID-19 vaccination, with hesitancy linked to concerns about effectiveness, safety, and necessity [ 62 ]. Communication programs focusing on individual benefits can increase vaccine intention and uptake.…”
Section: Discussionsupporting
confidence: 91%
“…Communication programs focusing on individual benefits can increase vaccine intention and uptake. Healthcare authorities can target hesitant parents through campaigns and endorsements, while using validated vaccine hesitancy scales to measure hesitancy consistently and develop targeted interventions [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review identified parental age as one of the main factors described in 9 (out of 23) studies, influencing parents' intention to vaccinate their children against COVID-19. However, this is hard to interpret as out of the 23 included studies, only three studies (16,19,21) included age as a continuous variable. The remaining studies categorized age into different age categories without providing a valid rationale for such a categorization.…”
Section: Discussionmentioning
confidence: 99%
“…Altulaihi and colleagues described that the presence of extended family support was linked to parents' willingness to vaccinate their children against COVID-19 (8). Other factors included the mutual involvement of both parents in decisions regarding the child's care (16) and the type of COVID-19 vaccine to be given to the child (21).…”
Section: Determinants Of Parental Attitudes and Hesitancy Toward Covi...mentioning
confidence: 99%
“…Advised by the Saudi Ministry of Health (MOH) and international health organizations, the government launched its vaccination campaign in December 2020, adopting a phased approach that focused initially on high-risk groups and healthcare workers. In August 2021, the government opened vaccination eligibility to all adults aged 18 years and above [ 15 ]. The vaccination program involved procuring and distributing various COVID-19 vaccines as they received regulatory approval, including those developed by Pfizer-BioNTech, AstraZeneca, Moderna, and others [ 16 ].…”
Section: Introductionmentioning
confidence: 99%